Gut microbiome alterations in ICU patients with enteral nutrition-related diarrhea - Ni, Weiwei; Jiao, Xinwei; Zou, Huihuang; Jing, Mengjuan; Xia, Ming; Zhu, Shichao; Li, Liming (Frontiers in Microbiology, 2022)
Enteral Nutrition-related Diarrhea (END) is an extremely common complication in Intensive Care Unit (ICU) patients. However, it is currently unclear whether the patient’s gut microbiota is disturbed. Our study aimed to explore the characteristics of gut microbiota changes in END patients. We divided ICU patients into no-END group (n = 7) and END group (n = 7) according to whether they had END, then stool samples were collected separately. The V3-V4 region of stool bacterial 16S rRNA gene was amplified by PCR and sequenced on an Illumina MiSeq PE300 platform. Microbiome data obtained by quality control were analyzed, including microbial community composition, diversity and gene function prediction.The results showed that the dominant gut microbiota in ICU patients who were given total enteral nutrition were Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, and Verrucomicrobia. Bacterial richness and diversity in END patients were all significantly lower than those in no-END patients. In addition, END caused significant changes in bacterial composition. LEfSe found 34 biomarkers represented by Bacteroidetes and Subdoligranulum in the no-END group as well as 11 biomarkers represented by Enterococcus and Klebsiella in the END group. Finally, through PICRUST function prediction, we found that diarrhea led to abnormal changes in numerous KEGG pathways mainly related to immunity and metabolism. In short, ICU patients with END have severe gut dysbiosis, and our study provides a reliable experimental basis for the patient’s microbiota therapy.